Combined spinal epidural anaesthesia versus epidural anaesthesia: a comparative study - Shrestha, Pramesh Sunder; Shrestha, Ninadini; Shrestha, Anil; Amatya, Roshana; Shakya, Bigen Man; Karki, Bipin (Journal of Chitwan Medical College, 2020)
Background: Regional anaesthesia are widely utilized in surgical gynaecology practice. The Combined Spinal Epidural Anaesthesia (CSEA) technique and Continuous epidural anaesthesia both have been extensively used in elective gynaecological surgeries. This prospective cross-sectional comparative study was designed to compare the quality of anaesthesia between CSEA and Epidural anaesthesia. Methods: Sixty-four patients between age group 15- 65 years of ASA grade I, II were randomly divided into 2 groups. Group A patients received CSEA using “double needle double interspace technique” and were given 2.5 ml of 0.5% hyperbaric bupivacaine for spinal block. Group B patients received epidural block with catheter using 10 ml of 0.5% plain bupivacaine. In all patients, subsequent dosage of 2 ml per unblocked segment 0.5% plain bupivacaine was administered through the epidural catheter to achieve a block up to T4-5. Mean was calculated using t-test, median with Mann Whitney U test and Chi-square test where appropriate and the Statistical Analysis was done using SPSS program, version 11.0. Results: The surgical anaesthesia and motor blockade occurred significantly early in CSEA group. Duration of analgesia was significantly shorter in CSEA (84.1±40.6 min) as compared to epidural group (138.6±32.9 min). The total amount of bupivacaine required to attain the same target level was two times in epidural group (p<0.05). Haemodynamic changes were comparable in both the groups. No neurological side effects were observed. Conclusions: Sequential CSEA is superior alternative to epidural block, which combines the advantages of spinal and epidural while minimizing their drawbacks in elective gynaecological surgeries.